Rotavirus vaccine and health-care utilization for rotavirus gastroenteritis in Tsu City, Japan - Kazutoyo Asada; Hajime Kamiya; Shigeru Suga; Mizuho Nagao; Ryoji Ichimi; Takao Fujisawa; Masakazu Umemoto; Takaaki Tanaka; Hiroaki Ito; Shigeki Tanaka; Masaru Ido; Koki Taniguchi; et al. (World Health Organization Regional Office for the Western Pacific, 2016)
Background: Rotavirus vaccines were introduced in Japan in November 2011. We evaluated the subsequent reduction of the health-care burden of rotavirus gastroenteritis. Methods: We conducted active surveillance for rotavirus gastroenteritis among children under 5 years old before and after the vaccine introduction. We surveyed hospitalization rates for rotavirus gastroenteritis in children in Tsu City, Mie Prefecture, Japan, from 2007 to 2015 and surveyed the number of outpatient visits at a Tsu City clinic from 2010 to 2015. Stool samples were obtained for rotavirus testing and genotype investigation. We assessed rotavirus vaccine coverage for infants living in Tsu City. Results: In the pre-vaccine years (2007-2011), hospitalization rates for rotavirus gastroenteritis in children under 5 years old were 5.5, 4.3, 3.1 and 3.9 cases per 1000 person-years, respectively. In the post-vaccine years (2011-2015), the rates were 3.0, 3.5, 0.8 and 0.6 cases per 1000 person-years, respectively. The hospitalization rate decreased significantly in the 2013-2014 and 2014-2015 seasons compared to the average of the seasons before vaccine introduction (p < 0.0001). In one pre-vaccine year (2010-2011), the number of outpatient visits due to the rotavirus infection was 66. In the post-vaccine years (2011-2015), the numbers for each season was 23, 23, 7 and 5, respectively. The most dominant rotavirus genotype shifted from G3P[8] to G1P[8] and to G2P[4]. The coverage of one dose of rotavirus vaccine in Tsu City was 56.5% in 2014. Conclusion: After the vaccine introduction, the hospitalization rates and outpatient visits for rotavirus gastroenteritis greatly decreased.